Knowledge About Hospice: Exploring Misconceptions, Attitudes, and Preferences for Care. (February 2016) - Cagle, John G.; Van Dussen, Daniel J.; Culler, Krystal L.; Carrion, Iraida; Hong, Seokho; Guralnik, Jack; Zimmerman, Sheryl
Context: Poor knowledge and misperceptions about hospice are believed to be common, but there is scant evidence about the public's understanding of hospice. Objectives: To examine hospice knowledge among geographically diverse adults; and describe linkages between knowledge, attitudes and beliefs about hospice care, and demographics. Methods: A small cross-sectional telephone survey of adults living in the contiguous US was conducted using randomly selected numbers (cell phone and landline) and over-sampling of minorities. Measures assessed knowledge (23-item test), attitudes (8-item scale), experiences and preferences related to hospice. Results: 123 participants completed surveys (response rate 46%). 106 (86%) had heard about hospice, 65 (54%) of whom had a personal experience with hospice. Participants had an average hospice knowledge test score of 18 (SD = 3.4) indicating moderate knowledge of hospice. A majority of respondents (62%) did not know that hospice cannot provide concurrent cure-oriented care. Misperceptions about eligibility, coverage of hospice, the provision of hospice in nursing homes or to persons who live alone were not uncommon (missed by >20%). Greater knowledge of hospice was associated with more favorable attitudes about the hospice philosophy of care (r = .22, p = .023) and a greater preference for hospice (p = .049). Respondents who were more educated, worked in the medical field, were non-Hispanic White, and had direct experience with hospice were also more likely to be more knowledgeable about hospice. Conclusion: Despite relatively high hospice awareness and favorability, myths and misperceptions about hospice still abound – and may drive ethnic disparities in end-of-life care. Educational interventions and future study are needed.